2021
DOI: 10.3390/polym13152409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Conditions on the Properties of Resorcinol-Formaldehyde Aerogel Microparticles Produced via Emulsion-Gelation Method

Abstract: Organic aerogels in the form of powder, microgranules and microsized particles receive considerable attention due to their easy fabrication, low process time and costs compared to their monolithic form. Here, we developed resorcinol-formaldehyde (RF) aerogel microparticles by using an emulsion-gelation method. The main objective of this study is to investigate the influence of curing time, stirring rate, RF sol:oil ratio and initial pH of the sol in order to control the size and properties of the microparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Further, increasing the DDA addition to 2.68 mmol reduced the H 2 O 2 yield. Research has shown that the formation of clusters in the gel step was controlled via the amount of proton amines, which further affects the porosity of the catalyst. , As shown in Figure S6, all samples displayed type IV isotherms of N 2 adsorption–desorption, suggesting the coexistence of mesoporous, macroporous, and microporous structures. The specific surface area and pore volume of PCMs decreased in the order of 2.68 mmol < 0.68 mmol < 0 mmol, indicating that DDA can reduce network clusters and porosity (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Further, increasing the DDA addition to 2.68 mmol reduced the H 2 O 2 yield. Research has shown that the formation of clusters in the gel step was controlled via the amount of proton amines, which further affects the porosity of the catalyst. , As shown in Figure S6, all samples displayed type IV isotherms of N 2 adsorption–desorption, suggesting the coexistence of mesoporous, macroporous, and microporous structures. The specific surface area and pore volume of PCMs decreased in the order of 2.68 mmol < 0.68 mmol < 0 mmol, indicating that DDA can reduce network clusters and porosity (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The perfluorosulfonated membrane spectra analysis shows a typical fingerprint as reported in literature [ 43 , 44 , 45 ]: 551 cm −1 associated with torsion and bending vibrations t (CF 2 ); 626–653 cm −1 associated with rotation vibrations (CF 2 ); 717 cm −1 associated with symmetry vibrations (CF2); 805 cm −1 associated with (C–S) vibrations; 963–980 cm −1 associated with (C–O–C) vibrations; 1059 cm −1 associated with symmetry vibrations (SO3-); 1127 cm −1 associated with asymmetry vibrations (SO3-); 1150–1243 cm −1 associated with asymmetry vibrations (CF2); 1300–1319 cm −1 associated with (C–C) vibrations; and 1471 cm- 1 associated with asymmetry vibrations of (SO3H). In PFSA–RF spectra, an RF-resin-specific response could be identified: 1646 and 1490 cm −1 associated with C=C aromatic benzene ring stretching and scissor vibrations, respectively; 1380, 1311, and 1297 cm −1 associated with O–H in-plane bending; 1167 and 1152 cm −1 associated with C–O symmetric and asymmetric stretching, respectively; 1077 cm −1 associated with the C–O–C linkage stretching vibrations of methylene ether bridges between two resorcinol molecules; and 773,740 cm −1 associated with C–H aromatic group stretching and out of plane bending [ 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%